SWOT Analysis in Determining Marketing Strategy for Lhewy's Kitchen Business - Nonik, Nonik; Septriani, Ester Kerina (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to analyze marketing strategies at Lhewy’s Kitchen, a micro, small, and medium enterprise (MSME) engaged in the culinary sector, using the SWOT analysis framework. Data were collected through interviews with the business owner, direct observation, and supporting documentation. The research employed a qualitative descriptive method, focusing on the identification of internal and external factors that affect the business. Internal factors (strengths and weaknesses) and external factors (opportunities and threats) were assessed through the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The results show that Lhewy’s Kitchen has a strong internal position with a total IFAS score of 2.42 and effectively responds to external factors with an EFAS score of 2.65. Based on the SWOT matrix, the recommended strategies include expanding distribution through consignment with local stores and cooperatives, optimizing online sales channels, increasing the workforce by implementing commission-based incentives, and enhancing promotional activities on social media. These strategies are expected to strengthen competitiveness, improve sales performance, and support the sustainability of Lhewy’s Kitchen in a highly competitive food industry.